Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
The solution to the quadratic equation be:
[tex]x=\frac{5}{3},\:x=-1[/tex]
Step-by-step explanation:
Given the expression
3x² – 2x = 5
Solving with the quadratic formula
[tex]3x^2-2x=5[/tex]
subtract 5 from both sides
[tex]3x^2-2x-5=5-5[/tex]
Simplify
[tex]3x^2-2x-5=0[/tex]
For a quadratic equation of the form ax²+bx+c=0
[tex]x_{1,\:2}=\frac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]
For a = 3, b = -2, c = -5
[tex]x_{1,\:2}=\frac{-\left(-2\right)\pm \sqrt{\left(-2\right)^2-4\cdot \:3\left(-5\right)}}{2\cdot \:3}[/tex]
[tex]x_{1,\:2}=\frac{-\left(-2\right)\pm \:8}{2\cdot \:3}[/tex]
Separate the solutions
[tex]x_1=\frac{-\left(-2\right)+8}{2\cdot \:3},\:x_2=\frac{-\left(-2\right)-8}{2\cdot \:3}[/tex]
solving
[tex]x_1=\frac{-\left(-2\right)+8}{2\cdot \:3}[/tex]
[tex]=\frac{2+8}{2\cdot \:3}[/tex]
[tex]=\frac{10}{6}[/tex]
[tex]=\frac{5}{3}[/tex]
also solving
[tex]x_2=\frac{-\left(-2\right)-8}{2\cdot \:3}[/tex]
[tex]=\frac{2-8}{2\cdot \:3}[/tex]
[tex]=\frac{-6}{2\cdot \:3}[/tex]
[tex]=\frac{-6}{6}[/tex]
[tex]=-\frac{6}{6}[/tex]
[tex]=-1[/tex]
Therefore, the solution to the quadratic equation be:
[tex]x=\frac{5}{3},\:x=-1[/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.